Meningkatkan Kemampuan Keaksaraan Awal Melalui Permainan Syllable Board - Sopwandin, iwan; A’yuni, Annisa Qurota (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2024)
Early literacy abilities in this case include the ability to read letter symbols, read syllables, recognize vowels, recognize consonant letters, indicate letters according to their sounds and arrange syllables into words. This research aims to determine the increase in early literacy skills through the Syllable Board game. The Classroom Action Research (PTK) method was used in this research with a flow of planning, action, observation and reflection carried out in two cycles. The data collection techniques used are observation, documentation and interviews. The results of the research show that the early literacy abilities of TKIT Annida Sokaraja group B children increase in each cycle through the Syllable Board game. As for the increase in initial conditions or Pre-Cycle, the average percentage value was 58.89%, after implementing the Syllable Board game, the average value increased to 75.28% in Cycle I. After improvements were made in Cycle II, the average value the average increased to 87.5%.